2021
DOI: 10.1186/s40001-021-00499-6
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea reduces antibiotic usage in children through respiratory tract infection prevention: a randomized, blinded, controlled clinical trial

Abstract: Background In children, up to 30% of viral respiratory tract infections (RTIs) develop into bacterial complications associated with pneumonia, sinusitis or otitis media to trigger a tremendous need for antibiotics. This study investigated the efficacy of Echinacea for the prevention of viral RTIs, for the prevention of secondary bacterial complications and for reducing rates of antibiotic prescriptions in children. Methods Echinaforce® Junior table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 35 publications
3
50
0
2
Order By: Relevance
“…In another study, the same EF extract was administered for 2 × 2 months for prevention in children, interrupted with a one-week treatment break [19]. Consistent with our findings, Ogal (2020) observed significantly fewer infections with enveloped viruses in the Echinaforce group (OR = 0.43, p=0.0038), further substantiating the relevance of antiviral effects in vivo [19].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In another study, the same EF extract was administered for 2 × 2 months for prevention in children, interrupted with a one-week treatment break [19]. Consistent with our findings, Ogal (2020) observed significantly fewer infections with enveloped viruses in the Echinaforce group (OR = 0.43, p=0.0038), further substantiating the relevance of antiviral effects in vivo [19].…”
Section: Discussionsupporting
confidence: 84%
“…Assumptions for the power calculation were based on the pre-pandemic situation and did not take into account containment measures such as disinfection, wearing masks or social distancing. For example, influenza viruses were not observed in the current study and the demonstrated, preventive effects of Echinaforce for this particular virus could not be reproduced [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a second double-blinded multi-center RCT, the same Echinacea extract formulated in tablets was given to children 4 to 12 years old living in central Switzerland [34]. Here, the authors chose low-dose vitamin C 3x 50 mg/d as control.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the large number of Echinacea clinical trials we identified only two clinical studies that collected nasopharyngeal samples for virus testing [31,34]. Both studies accurately described blinding, randomization, were appropriately controlled and referred to data set from almost 1000 patients treated over a period of 4 months with either tincture or tablets from the same 65% (v/v) ethanolic extract from Echinacea purpurea .…”
Section: Discussionmentioning
confidence: 99%